INOVASI “NEW SAKPOLE” SEBAGAI STRATEGI PELAYANAN PUBLIK BERBASIS E-GOVERNMENT UNTUK PEMBAYARAN PAJAK KENDARAAN BERMOTOR DI JAWA TENGAH - Faris Budiman; Retno Sunu Astuti (JURNAL ILMIAH EDUNOMIKA, 2021)
The problem raised in this study is how the innovation of "New Sakpole" as an e-government-based public service strategy for motor vehicle tax payments in Central Java. Based on the formulation of the problem, this study aims to describe the "New Sakpole" innovation as an e-government-based public service strategy for the payment of motor vehicle taxes by the Central Java Government. The theory used in this research is the theory of public policy and innovation. This study uses a qualitative approach with a descriptive method. The data analysis technique used is qualitative analysis (data reduction, presentation and conclusion). The results of the study indicate that "New Sakpole" is an innovation of the Central Java government's public policy in terms of encouraging people to be obedient and disciplined in paying motor vehicle taxes. This policy is very effective because it can cut people's time and energy, and does not cause crowds of people. The public policy of "New Sakpole" as one of the innovations of the Central Java government is a breakthrough that has never been done by other governments. This policy can be imitated by other governments in order to boost the income of the tax sector, especially the motor vehicle tax sector.